(untitled) (Teaching and Learning Inquiry, 2021)
The need to make higher education curricula gender-inclusive is increasingly pressing as student cohorts diversify. We adopted a student-staff partnership approach to design, integrate, and evaluate a module that taught first-year science students the difference between biological sex, gender identity, gender expression, and sexual orientation in the context of genetics concepts at an Australian university. This module aimed to break the binary in misconceptions of both sex and gender, emphasising that both exist on separate spectra. Data triangulation was used to evaluate students’ attitudes towards the module and their learning of module concepts. Students’ attitudes were positive overall, and evaluation of students’ learning indicated that the majority of students understood and retained key concepts, while also identifying common misconceptions. Perhaps the most important finding was that students who identified as belonging to a minority group had significantly more positive attitudes towards the module than non-minority students. This finding supports previous research that has found inclusive curricula have greater benefit for students from minority backgrounds, indicating the importance of making such curriculum enhancements. Our results speak to both the co-creation process and students’ learning outcomes, providing valuable insights for practitioners both within science and beyond.